Anisakis Allergy: Raising Awareness - Rama, Tiago Azenha (2022)
Introduction: Ingestion of Anisakis is a common cause of allergic reactions to seafood in countries in which undercooked/raw seafood is part of gastronomic traditions. Despite current trends for the ingestion of raw/marinated/undercooked fish, the prevalence rate of anisakiasis and allergy to Anisakis is still considered to be low in Portugal. We aimed to review the current pathogenic mechanisms, the clinical and diagnostic approach of Anisakis allergy, and Anisakis-related eviction measures, while raising awareness to this problem. Material and Methods: Literature search in the MEDLINE and Scopus databases, regarding Anisakis allergy. Conclusion: Assessment of sensitization to Anisakis should be included in the workup study of urticaria/angioedema and anaphylaxis, as there is a rise in consumption of raw and undercooked fish. Ingestion of previously frozen and properly cooked fish appears to be safe for most patients who are allergic to Anisakis.